DETERMINATION OF HYDROCARBON ZONE AND DEPOSITIONAL ENVIRONMENT FACIES IN TALANG AKAR FORMATION, SOUTH SUMATRA BASIN AT "EPURA" FIELD - KAMILA, PUTRI; Sunardi, Edy; Sendjadja, Yoga Andriana; Pranopto, Andri; Herida, Shaskia (Journal of Geological Sciences and Applied Geology, 2023)
The EPURA field is one of the oil and gas producing fields in the South Sumatra Basin, where well completion has been carried out in the Talang Akar Formation, and the production test results are interpreted to mean that in wells EP-13, EP-14, EP-15, EP-16, EP-17 and EP-23 contain several reservoir zones that have the potential to contain hydrocarbons. This research with facies interpretation analysis uses data from six wells (wireline, mudlog, RCAL and lithology data), so it is hoped that it can provide more detailed information for the development of an oil and gas field. The analysis carried out is in the form of facies analysis, depositional environment, electrofacies and facies correlation. From the research results, it was found that the Talang Akar Formation has depositional facies in the form of a fluvial, which in this study is the Lower Talang Akar Formation with depositional facies in the form of channel, Crevasse Splay, point bar and flood plain. Based on the analysis results, the Talang Akar Formation is divided into 3 reservoir zones, namely Zone EP-1, EP-2, and EP-3. After going through all stages of petrophysical analysis, it was found that zones with high hydrocarbon potential were found in wells EP-13, EP-23 and EP-16. The wells with low hydrocarbon potential are EP-14, EP-15 and EP-17 wells. The zone of highest hydrocarbon potential in prospect wells is in the EP-1 zone with a Crevasse Splay facies association and has thick sandstone lithology characteristics with medium to fine grain size.